EVALUASI PERENCANAAN KEBUTUHAN OBAT PUBLIK SERTA KETERSEDIAAN OBAT DI TINGKAT PUSKESMAS SE-WILAYAH KERJADINKES KOTA SURAKARTATAHUN 2015 - Eko Yudha Prasetyo; Satibi .; Gunawan Pamudji Widodo (Jurnal Farmasi Indonesia, 2016)
Drug planning is an important aspect of drug management. Planning is aimed at determining the type and amount of drug in accordance with the needs of community helth center. Although the regulatory guideline of public drug management have been made, but still found the incidence of overstock and stockout. With these considerations it’s necessary to evaluate related planning processes and drug availability. The purpose of this study to know the planning process, the problems encountered and the level of drug availability in community health center throughout the whole working area of Surakarta Department of Health. This research is observational and evaluative study with qualitative approach, supported by quantitative data. Secondary data were obtained from the search document of drug plan for 2015, the usage and demand report of drug. The secondary data is processed to determine the accuracy of planning, the availability and suitability of drug demand. To strengthen information were conducted triangulation and interviews with drug manager related. The results showing the drug plan has not been efficient seen from an average accuracy of drug planning in treatment primary health centers is 440.5% and 389.98% at non-treatment primary health centers. The problems in planning isn’t optimal use of information management system based on electronically in providing data for drug planning, the procurement with e-purchasing requires time and administration are too long, the plan of medicine isn’t fully realized, the community health center received drug beyond the plan so that the use of drugs less effective, The average availability of drugs in the category of excess which amounted to 31.13 months in treatment health centers and 33.95 months in non-treatment.